Psychological Well-Being of Adolescents Experiencing Bullying: The Role of Family Functioning, Friendship Quality, and Resilience - Sholikhah, Tri Pujiati; Lestari, Sri (Journal of Educational, Health and Community Psychology, 2025)
Adolescent victims of bullying often struggle to socialize and often experience some unpleasant feeling such as sense of uselessness, lack of confidence, anxiety, loneliness, sadness, and even suicide attempt. This study sought to investigate how family functioning, friendship quality, and resilience influence the psychological well-being of adolescents who had been bullied. This quantitative study involved 371 junior high school adolescents from Surakarta who had experienced bullying. Data were gathered using a validated family functioning measure, friendship quality scale, resilience scale, and psychological well-being scale. The data were then analyzed using the Structural Equation Model Partial Least Squares (SEM-PLS). The findings suggest that despite their low predictive accuracies, all three variables have great predictive power and may considerably explain the effect of predictor factors on the adolescents’ psychological well-being of who are bullied. Current study's practical implications include that stakeholders, such as parents, teachers, and psychology practitioners, should pay attention to and develop these qualities in order to enhance the psychological well-being of adolescents who are bullied.